2019
DOI: 10.1002/ijc.32588
|View full text |Cite|
|
Sign up to set email alerts
|

GPER‐induced signaling is essential for the survival of breast cancer stem cells

Abstract: G protein‐coupled estrogen receptor‐1 (GPER), a member of the G protein‐coupled receptor (GPCR) superfamily, mediates estrogen‐induced proliferation of normal and malignant breast epithelial cells. However, its role in breast cancer stem cells (BCSCs) remains unclear. Here we showed greater expression of GPER in BCSCs than non‐BCSCs of three patient‐derived xenografts of ER−/PR+ breast cancers. GPER silencing reduced stemness features of BCSCs as reflected by reduced mammosphere forming capacity in vitro, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 49 publications
0
34
1
Order By: Relevance
“…Protein phosphorylation is central to the understanding of downstream signaling pathways responsible for regulating stem cell functions. Quantitative phosphoproteomics has been used to study global signaling events in pluripotent, and cancer stem cells and new therapeutic targets have accordingly been proposed ( 59 62 ). To our knowledge, however, it has not been used before to assess the impact of inflammation on stem cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphorylation is central to the understanding of downstream signaling pathways responsible for regulating stem cell functions. Quantitative phosphoproteomics has been used to study global signaling events in pluripotent, and cancer stem cells and new therapeutic targets have accordingly been proposed ( 59 62 ). To our knowledge, however, it has not been used before to assess the impact of inflammation on stem cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Several observations strongly support that it is. First, GPER is required for the survival of xenograft-derived cancer stem cells and metastatic disease (59). Second, in breast cancer cells, GPER integrates assembly of the fibronectin matrix (60) with the release of EGF (61); thus satisfying two basic requirements or cellular survival: attachment to the extracellular matrix and responsiveness to growth factors.…”
Section: Gper In Metabolic Disease and Cancermentioning
confidence: 99%
“…In addition, the GPER-1/EGFR signaling axis mediates the expression of cell cycle regulatory genes in cancer-associated fibroblasts derived from breast cancer patients, favoring tumor progression (40). It has recently been shown that stimulation with tamoxifen, activates GPER-1, improving breast cancer stem cells viability and stemness and BAD phosphorylation, event that seems to be an alternative survival mechanism for these cells (51).…”
mentioning
confidence: 99%